Fish exports and economic growth: The case of SIDS - Jaunky, Vishal (Taylor & Francis, 2011)
The fishery sector is considered to be of vital importance by many economies in particularly the small island developing states (SIDS). The production and commercialization of fish constitute an important source of good protein, employment, and export revenues. Fish exports can indeed contribute to economic growth. This article attempts to explore the causal relationship between fish exports growth and economic growth for 23 SIDS over the period 1989-2002. Various panel unit root and cointegration tests are applied. Results show strong evidence of a long-run relationship between the growth of fish exports and economic growth. In addition, the Blundell-Bond system generalized methods-of-moments (GMM) method is utilized to conduct a Granger-type causality test within a vector autoregressive (VAR) panel data framework. Bi-directional causality is uncovered in the long run, implying a virtuous cycle between fish export and economic growth. The long-run estimate of the impact of the fish export growth on economic growth is calculated by employing the panel fully modified ordinary least squares (FMOLS) method and is found to be 0.01. These results show that fish exports represent a means for the SIDS to sustain their economic growth over the long run and the importance for them to manage their fisheries. © Taylor & Francis Group, LLC.